Good Outcome of Resective Epilepsy Surgery in a 1-Year-Old Child with Drug-Resistant Focal Epilepsy with a Novel Pathogenic COL4A1 Mutation - Fearns, Nicholas; Wagner, Matias; Borggräfe, Ingo; Kunz, Mathias; Rémi, Jan; Vollmar, Christian (Neuropediatrics, 2024)
Pathogenic variants in COL4A1, encoding the α chain of type IV collagen, have been associated with cerebrovascular pathology as well as malformations of cortical development, thereby causing structural epilepsy. This case illustrates successful resective epilepsy surgery in a 12-month-old girl with left occipital focal cortical dysplasia (FCD) associated with a heterozygous splice-donor variant in COL4A1. She presented with drug-resistant focal epilepsy with daily seizures from the age of 2 months, refractory to several combinations of antiseizure medications, as well as mild right-sided hemiparesis and developmental delay. All presurgical diagnostic modalities, including ictal and interictal electroencephalography, magnetic resonance imaging, and ictal fluorodeoxyglucose positron emission tomography, showed congruent findings, pointing toward one single left occipital epileptogenic zone (EZ). We performed a left occipital lobectomy, using intraoperative electrocorticography to confirm the boundaries of the EZ. After surgery, the patient has remained seizure free, and both cognitive and motor developments have improved. Histopathology of the resected brain tissue showed FCD type Ia. Resective epilepsy surgery can have a very good outcome, also in patients with genetic mutations in COL4A1, constituting a less invasive option than the previously used more radical surgical procedures such as hemispherectomy.
Keywords: genetic epilepsies; focal cortical dysplasia; malformations of cortical development; collagen; FCD